Local administration of social assistance programs in Russia - Richman, Burton; Struyk, Raymond (2002)
Competent administration is fundamental to successful reform of social assistance programs in transition economies. Only with such administration is there assurance that benefits are being delivered as intended in enabling legislation. Moreover, the perceived efficiency and fairness of administration influences the public's views of the new programs. In the Russian Federation local governments have primary responsibility for the administration of social assistance programs enacted by all levels of government. This paper presents the results of surveying nine offices charged with administering social assistance programs in four Russian municipalities. The accent is on the basics of program administration and management. Topics studied include client flow, eligibility verification procedures, the presence of a procedures manual for in-take workers, quality control procedures, and training. The findings are sobering and emphasize the need for the Russian government to assist municipalities to strengfthen their administrative capacity through a combination of exhortation and leadership, provision of written guidance materials - on good administrative practices and program-specific regulations and procedures - and a national program of seminars for supervisors of various programs. - Reproduced.
Keywords: Social services - Russia; Local government - Russia; Local government